2020
DOI: 10.3390/genes12010004
|View full text |Cite
|
Sign up to set email alerts
|

APOE Variants in an Iberian Alzheimer Cohort Detected through an Optimized Sanger Sequencing Protocol

Abstract: The primary genetic risk factor for late onset Alzheimer’s disease (LOAD) is the APOE4 allele of Apolipoprotein E (APOE) gene. The three most common variants of APOE are determined by single nucleotide polymorphisms (SNPs) rs429358 and rs7412. Our aim was to estimate allele and genotype frequencies of APOE variants in an Iberian cohort, thus helping to understand differences in APOE-related LOAD risk observed across populations. We analyzed saliva or buccal swab samples from 229 LOAD patients and 89 healthy el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…To correlate a possible genetical predisposition and a significant risk of developing cognitive impairment, we performed an APOE genotyping for SNPs rs429358 and rs7412 in those patients, which are widely discussed in the literature as responsible for increasing the risk of dementia and cognitive impairment ( 39 42 ). APOEs play a vital role in lipid transport and metabolism, thus influencing the risk of cardiovascular disease ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…To correlate a possible genetical predisposition and a significant risk of developing cognitive impairment, we performed an APOE genotyping for SNPs rs429358 and rs7412 in those patients, which are widely discussed in the literature as responsible for increasing the risk of dementia and cognitive impairment ( 39 42 ). APOEs play a vital role in lipid transport and metabolism, thus influencing the risk of cardiovascular disease ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major single genetic risk factor for late-onset Alzheimer’s disease is the apolipoprotein ( APOE ) ε4 allele. In addition to optimising APOE sequencing, Gonzalez et al [ 5 ] found allele differences in the ε4 and ε2 alleles in late-onset Alzheimer’s disease cases between Spanish and Portuguese subsamples, highlighting the importance of considering different ancestries and diverse populations when undertaking these studies.…”
mentioning
confidence: 99%